أثر نظام الحماية الالكتروني في الحد من مخاطر تكنولوجيا المعلومات و الاتصال دراسة مقارنة لعينة من المؤسسات - عطية, العربي; رجم, خالد; بن عمارة, الطاهر (University of Eloued جامعة الوادي, 2018)
هدفت هذه الدراسة الى تقييم مدى مساهمة نظام الحماية الكتروني في الحد من مخاطر تكنولوجيا المعلومات و الاتصال دراسة مقارنة لعينة من المؤسسات في ولاية ورقلة، حيث تم الاعتماد على المنهج الوصفي باستخدام كل من أداة المقابلة و الاستبيان حيث تمثلت عينة الدراسة في ثلاثة مؤسسات اتصالات الجزائر ،سونلغاز، ليند غاز، بمجمل 228 استبيان موجه إلى مسيري و مستخدمي تكنولوجيا المعلومات والاتصال في المؤسسة، وكانت نسبة الاستجابة 97% ،كما تم الاعتماد في التحليل البيانات الاستبانة على برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS و كانت أهم النتائج المتوصل إليها هي : تتعرض المؤسسات إلى عدة مخاطر تهدد أمن نظم المعلومات الإلكترونية، فاعلية السياسات الأمنية و ضوابط للموظفين داخل المؤسسة من شأنه ضمان الحد من مخاطر استخدام تكنولوجيا المعلومات والاتصال بالإضافة الى أن عملية التكوين في مجال الأمن الكتروني في المؤسسات به عدة اختلالات ونقائص انطلاقا من تحديد الاحتياجات التكوين في حد ذاته، وأخيرا ليزال موظفي المؤسسات محل الدراسة يعانون من نقص على مستوى الثقافة التكنولوجية، اضافة الى عدم وجود صرامة بشأن احترام القواعد واللوائح القانونية المتعلقة بنظام الأمن الالكتروني. Abstract: The aim of this study is to assess the extent to which the electronic protection system contributes to the reduction of information and communication technology risks with a comparative study of a sample of institutions in the state of Ouargla. The present study relied on the descriptive method using both the interview tool and the questionnaire. The study sample was consisted of three institutions Algeria Telecom, Sonelgaz, and Lindh Gas, in which 228 questionnaires were addressed to the information and communication technology managers and users in these institutions, and the response rate was 97%. The analysis of the questionnaire data was also based on the SPSS program and the most important results are: firstly, the institutions are exposed to several risks threaten the security of the electronic information systems. Then, the effectiveness of security policies and the controls of staff within the institution will ensure the reduction of the risk of the information and communication technology use; in addition, the process of training in the field of electronic security in the institutions has several imbalances and imperfections from the needs identification of the formation itself. Finally, the staff of the institutions concerned are still deficient in the level of technological culture, in addition to the lack of rigor regarding respect of the rules and regulations concerning the electronic security system.
The impact of the electronic protection system in reducing the risks of information and communication technology, a comparative study of a sample of institutions
مجلة رؤى المجلد الثامن العدد الثاني
Keywords: كنولوجيا المعلومات و الاتصال ; نظام الحماية الالكتروني ; مخاطر تكنولوجيا المعلومات و الاتصال ; سياسات الأمنية; Information and communication technology, information systems security, security policies, information and communication technology risks. (JEL) Classification: M15